KORELASI PERSEPSI SISWA TENTANG KOMPETENSI PROFESIONAL DAN KOMPETENSI PEDAGOGIK GURU PAI DENGAN MINAT DAN PRESTASI BELAJAR SISWA DI SMA BUNTOK KABUPATEN BARITO SELATAN PROVINSI KALIMANTAN TENGAH - Gazali, Achmad (STIT Ibnu Rusyd Tanah Grogot, 2022)
Learning achievement in PAI subjects is the goal of the entire process of education and teaching of Islam in schools so that efforts to improve student achievement require efforts to increase the supporting factors. Among them are the competence factors of PAI teachers, especially pedagogic competence and professional competence. Another factor is interest which is also an intervening variable in improving student achievement, namely increasing student interest in the competence of PAI teachers so that with the emergence of interest or higher student interest, student achievement will increase. In this case competence seems to have a relationship with student interest because it is the teacher's effort to generate and develop student interest by increasing their competence as a professional teacher. This study seeks to examine whether there is a correlation between students' perceptions of the pedagogic competence and professional competence of Islamic Religious Education teachers increasing interest in learning and whether there is a correlation between increased interest and learning achievement with the formulation of the problem: 1) Is there a correlation between students' perceptions of pedagogical competence and learning achievement ?, 2) Is there a correlation between students' perceptions of pedagogical competence and learning interest?, 3) Is there a correlation between students' perceptions of professional competence and learning achievement?, 4) Is there a correlation between students' perceptions of professional competence and learning interest?, 5) Is there a correlation? student perceptions of interest in learning and learning achievement, 6) Is interest in learning an intermediate variable between student perceptions of pedagogical competence and learning achievement?, 7) Is interest in learning an intermediary variable correlating student perceptions of professional competence with learning achievement. With the aim of knowing: 1) Correlation of students' perceptions of pedagogic competence with learning achievement, 2) Correlation of student perceptions of pedagogic competence with learning interest, 3) Correlation of student perceptions of professional competence with learning achievement, 4) Correlation of student perceptions of professional competence with interest in learning, 5) Correlation of students' perceptions of interest in learning with learning achievement, 6) Interest in learning is an intermediary variable between students' perceptions of pedagogic competence and learning achievement, 7) Interest in learning is an intermediary variable correlation of students' perceptions of professional competence with learning achievement. From the formulation of the problem and research objectives related to the theoretical basis, hypotheses can be put forward, namely: 1) There is a correlation between students' perceptions of pedagogical competence and learning achievement, 2) There is a correlation between students' perceptions of professional competence and learning interest, 3) There is a correlation of perceptions students about pedagogic competence with learning interest, 4) There is a correlation between students' perceptions about pedagogic competence and learning achievement, 5) There is a correlation between students' perceptions about learning interest with learning achievement, 6) Interest in learning is an intermediary variable between the correlation of students' perceptions about professional competence with achievement learning, and 7) interest in learning is an intervening variable between the correlation of students' perceptions of pedagogical competence and learning achievement. After being analyzed and presented in the discussion, the researchers found that there was a significant correlation between pedagogic competence and learning achievement, there was a significant correlation between professional competence and learning achievement, there was a significant correlation between pedagogic competence and interest in learning, there was a significant correlation between pedagogic competence and interest in learning, there is a significant correlation between learning interest and learning achievement. Interest in learning is an intervening variable that has a significant correlation between professional competence and learning achievement, and interest in learning is an intervening variable that has a significant correlation between pedagogical competence and learning achievement. From the results of this study it can be concluded that interest is a determining factor for improving learning achievement because with a strong interest, students' enthusiasm to study PAI will be more active.